2015
DOI: 10.1159/000439347
|View full text |Cite
|
Sign up to set email alerts
|

Bisphosphonate-Mediated Oral Ulcers: A Rare Differential Diagnosis of Erosive Oral Lesions

Abstract: Oral bisphosphonates are widely used drugs for the treatment of various indications such as postmenopausal osteoporosis. Ulcerations of the upper gastrointestinal tract, predominantly reported for alendronate, are common side effects. The occurrence of ulcerations within the oral cavity is less well known and probably underreported. Especially in cases of incorrect mode of intake, oral bisphosphonates are prone to induce oral ulcerations by as yet incompletely delineated mechanisms. We herein report on 2 elder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 21 publications
1
23
0
1
Order By: Relevance
“…Moreover, it has been reported that fluvastatin, an HMG‐CoA reductase inhibitor, and ZOL have synergistic cytotoxic effects in pancreatic cancer cell lines . Oral bisphosphonate‐induced gastric damages are partly caused by interference with the mevalonate pathway . Magierowski et al .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been reported that fluvastatin, an HMG‐CoA reductase inhibitor, and ZOL have synergistic cytotoxic effects in pancreatic cancer cell lines . Oral bisphosphonate‐induced gastric damages are partly caused by interference with the mevalonate pathway . Magierowski et al .…”
Section: Discussionmentioning
confidence: 99%
“…Many case reports have been published regarding the association between the oral bisphosphonate alendronate and oral ulceration . Oesophageal and gastrointestinal ulceration are well‐established side effects of alendronate, but oral ulceration is less widely known .…”
Section: Drug‐associated Mucosal Ulceration Mucositis and Bullous DImentioning
confidence: 99%
“…44 Many case reports have been published regarding the association between the oral bisphosphonate alendronate and oral ulceration. 45,46 Oesophageal and gastrointestinal ulceration are well-established side effects of alendronate, but oral ulceration is less widely known. 45 Many case reports attribute the development of oral ulceration with incorrect use of the medication, where the patient keeps the tablet in the mouth for a prolonged period instead of immediately swallowing it.…”
Section: Drug-associated Aphthous-like Ulcerationmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, diagnostic suspect of BRONJ must be supported by radiological investigation: the most frequently used radiological investigations are, on a first level, the panoramic x-ray and the intraoral x-ray and on a second level the computer tomography scan (CT), both spiral CT and cone beam CT (CBCT) (second level investigation) [8]. Other common side effects are ulcerations of the upper gastrointestinal tract, predominantly reported for alendronate in its oral administration [9], especially when patients have not taken BPs as instructed (lying down within 30 minutes of taking the medication). In addition, in 2009, a US Food and Drug Administration suggested an association between bisphosphonates and risk of oesophageal cancer [10] but, to date, the association between oral bisphosphonate use and upper gastrointestinal cancer has not been established [7].…”
Section: Introductionmentioning
confidence: 99%